Structured light and its applications : an introduction to phase-structured beams and nanoscale optical forces. - Andrews, David L., 1952- (Academic Press, 2008)
This contributed volume presents the latest in structured light and the non-contact optical manipulation of matter. It surges past mature technology and applications such as focused laser trapping and optical tweezers to optical vortices and holographic optical trapping. Andrews and his contributors shed light on technology and applications that extend to biological cell handling, laser cooling, atom trapping, and the control of Bose-Einstein condensates. With this book, the reader will be introduced to current developments in this field making this a must-own companion for anyone in the field or wanting to enter it. This all-inclusive treatise will include theory, generation methods, and applications of optical beams with these complex structures. Key aspects will be discussed such as wavefront structure, phase properties and photonic aspects of beam propagation. Opportunities abound through these optical forces and their complex fields. This book will lead the reader through all of the information to the core of the research and explain it thorouhly and directly. *Comprehensive and definitive source of the latest research in nanotechnology written by the leading people in the field *From theory to applications - all is presented in detail *Editor is Chair of the SPIE Nanotechnology Technical Group and is leading the way in generation and manipulation of complex beams.
Keywords: Beam optics.; Nanostructured materials -- Optical properties.; elektronické knihy; electronic books